Faktor-Faktor yang Mempengaruhi Nilai Perusahaan pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di BEI Periode 2016-2018 - Pratiwi Pardiastuti; Yuli Chomsatu Samrotun; Rosa Nikmatul Fajri (Owner : Riset dan Jurnal Akuntansi, 2020)
This study aims to analyze the factors that influence value company (PBV) which includes dividend policy (DPR), company size (SIZE), capital structure (DER), liquidity (CR), and profitability (ROA). The population in this study is a manufacturing company in the consumer goods industry sector listed on Indonesia Stock Exchange (IDX) for the period 2016-2018. The sampling technique uses the method purposive sampling, so we obtained a sample of 18 companies. Type quantitative research. Data sources in the form of secondary data. Data analysis used is multiple linear regression analysis. The results showed that partially dividend policy (DPR), capital structure (DER) and profitability (ROA) affect on value company (PBV). While the size of the company (SIZE) and liquidity (CR) has no affect on value company (PBV).